The Effect of Transfers and The Physical Work Environment on Employee Performance, With Job Satisfaction as An Intervening Variable, At Pt Smep Pacific - Sri Wahyuningsih; Tri Mulyani Kartini; Sindik Widati (Sean Institute, 2026)
This study examines the influence of job transfers and physical work environment on employee performance at PT SMEP PACIFIC, with job satisfaction as a mediating variable. The research focuses on the manufacturing sector, which is currently experiencing a decline in workforce productivity. The uniqueness of this study lies in the integration of job transfer and physical work environment variables within a single structural framework, with job satisfaction serving as a mediator. The selection of research location and timing adds contextual relevance to the organizational dynamics. A quantitative approach was employed, using primary data collected from 115 respondents through questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of LISREL 8.80 to examine the relationships among variables simultaneously. The results indicate that job transfers positively affect both job satisfaction and employee performance, directly and indirectly through the mediating role of job satisfaction. In contrast, the physical work environment does not directly influence job satisfaction but contributes to performance improvement indirectly. Some variables show significant roles in shaping performance, while others exhibit inconsistent effects. This study is limited to a specific sector and location, thus its findings may not be generalizable to broader contexts. The results offer practical insights for policymakers and industry practitioners in designing more adaptive job transfer strategies and managing work environments, while also serving as a reference for academics in developing human resource performance theories.